SISTEM PENYELENGGARAAN MAKANAN DI LEMBAGA PEMBINAAN KHUSUS ANAK KELAS II JAKARTA TAHUN 2021 (Analisis Kualitatif) - Diajeng Nurulita Novriprasasti (2021)
Based on research conducted by the Ministry of Health and the Ministry of Justice in 1990, it was stated that number of diseases related to nutrition in the inmates was 40.9%. This problem continues to be proven by the results of research which states that the nutritional value, taste, and portion of food in correctional institutions are less attention (Indonesia, 2009); (Muslimah et al., 2017) In addition, health service facilities in correctional institutions do not meet the standards (Firmansyah et al., 2019) The study used a qualitative descriptive approach through in-depth interviews and observation. Research informants consisted of the Head of LPKA Class II Jakarta, the Head of the LPKA Class II Jakarta Development Section, General Functional Positions for the Food Service Division, Doctors, Nurses, and several LPKA Class II Jakarta inmates. The results showed that the implementation of food and health services in LPKA Class II Jakarta is guided by UU No. 11 of 2012 concerning the Juvenile Criminal Justice System. In general, the implementation went well. However, several shortcomings were identified, including the taste of the food and the level of maturity of the food served to inmates are still below standard. There are shortages in health facilities and a limited supply of medicines at the polyclinic of LPKA Class II Jakarta.